Perencanaan Dan Perancangan Wellness Center Lansia Di Desa Bongkasa Pertiwi, Kabupaten Badung Dengan Pendekatan Biophilic Arsitektur: Bahasa Indonesia - Fahrul Nawan Subakti; Made Mas Surya Wiguna; I Wayan Wirya Sastrawan; I Kadek Merta Wijaya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
The increase in the number of elderly people and high levels of stress due to urbanization and modernization are problems that have an impact on the decline in quality of life, especially in the elderly group who experience physical limitations, mobility, and social interaction. This condition shows the importance of providing facilities that are able to support physical, mental, and social health in an integrated manner, so that the planning and design of the Elderly Wellness Center is a relevant solution to improve welfare holistically. This design is located in Bongkasa Pertiwi Village, Badung Regency, which has the potential for a natural environment that supports the concept of healing and relaxation. The approach used is biophilic architecture that integrates natural elements into the built environment to create a connection between humans and nature and have a positive impact on physical and psychological health. The methods used include literature studies, observations, and interviews to identify user needs and site conditions. The design results are realized through the concept of integrating natural elements such as natural lighting, ventilation, vegetation, and the relationship of indoor and outdoor spaces that support fitness activities, therapy, relaxation, and social interaction. This design is expected to be able to create a comfortable, safe, and inclusive environment for the elderly and become a reference in the development of similar facilities that are oriented towards environmental health and sustainability.